The Securitization Flash Flood - Srinivasan, Kandarp (The Review of Corporate Finance Studies, 2026)
This paper highlights a connection between the stability of a bank’s funding sources (debt claims) and the liquidity of assets backing those claims. Using a natural experiment and hand-collected data on over 5,000 repurchase contracts, the paper shows that a shock that increased the liquidity of private-label MBS resulted in a greater proportion of MBS financed on balance sheet by unstable funding sources (short-term repo debt). This finding is relevant to a recent banking crisis (the SVB collapse in March 2023) in which losses on a bank’s liquid assets led to a run by uninsured (“flighty”) depositors financing those assets. (JEL G2, K2)